Analysis of cribra orbitalia in the earliest inhabitants of medieval Vilnius - Jatautis, Šarūnas; Mitokaitė, Ieva; Jankauskas, Rimantas (Anthropological Review, 2011)
The purpose of this work is to present an analysis of cribra orbitalia (CO) from the population of a medieval cemetery in Vilnius, Lithuania, dated between the end of the 13th to the beginning of the 15th centuries. The sample consisted of 208 individuals with sufficiently preserved orbits: 82 subadults and 122 adults. CO was correlated with sex, age-at-death, and three skeletal indicators of biological health: linear enamel hypoplasia, periostitis, and adult femur length as a proxy value for stature. Siler's and Gompertz-Makeham's parametric models of mortality as well as χ2 statistics were used to evaluate these relationships. Almost one-third of all analyzed individuals had signs of CO, including approximately 60% of the subadults. There was a very strong relationship between the age-at-death and incidence of CO, i.e., individuals with the lesion were dying much younger. The frequency of CO among the sexes was not statistically significant. On the other hand, CO had a negative effect only on adult males, i.e., males who had the lesion died at a younger age. Furthermore, CO and linear enamel hypoplasia were positively related for subadults, whereas no significant relationships were found among adults of corresponding sex. Incidence of periostitis and adult stature were not related to CO.